Neutral red-mediated microbial electrosynthesis by Escherichia coli, Klebsiella pneumoniae, and Zymomonas mobilis. (November 2015) - Harrington, Timothy D.; Mohamed, Abdelrhman; Tran, Vi N.; Biria, Saeid; Gargouri, Mahmoud; Park, Jeong-Jin; Gang, David R.; Beyenal, Haluk
Highlights: Neutral red-mediated electrosynthesis was applied to three different bacteria. Electrosynthesis altered metabolite profiles in E. coli and K. pneumoniae . No effect was observed on Z. mobilis metabolites. Hypothesized NAD + reduction did not account for metabolite changes. Effects of electrosynthesis are consistent with a regulatory response. Abstract: The aim of this work was to compare the effects of electrosynthesis on different bacterial species. The effects of neutral red-mediated electrosynthesis on the metabolite profiles of three microorganisms: Escherichia coli, Klebsiella pneumoniae, and Zymomonas mobilis, were measured and compared and contrasted. A statistically comprehensive analysis of neutral red-mediated electrosynthesis is presented using the analysis of end-product profiles, current delivered, and changes in cellular protein expression. K. pneumoniae displayed the most dramatic response to electrosynthesis of the three bacteria, producing 93% more ethanol and 76% more lactate vs. control fermentation with no neutral red and no electron delivery. Z. mobilis showed no response to electrosynthesis except elevated acetate titers. Stoichiometric comparison showed that NAD + reduction by neutral red could not account for changes in metabolites during electrosynthesis. Neutral red-mediated electrosynthesis was shown to have multifarious effects on the three species.